Perlindungan Hukum Pembeli atas Ketidaksesuaian Kualitas Barang dan Jasa Berdasarkan Undang-Undang Perlindungan Konsumen - Hendro Ponco Raharjo; Cokorde Istri Dian Laksmi Dewi; I Wayan Putu Sucana Aryana (Syntax Corporation Indonesia, 2024)
The development of digital technology has encouraged changes in the way of buying and selling transactions, especially through e-commerce platforms. However, in practice, it is not uncommon for the goods and services purchased to not be in accordance with the quality promised by the seller. This study aims to analyze the implementation of Law No. 8 of 1999 concerning Consumer Protection in protecting buyers from non-conformities in the quality of goods and services. The research method used is a normative juridical approach with secondary data from literature reviews and related laws and regulations. The results of the study show that legal protection for consumers has been regulated, but its implementation still needs to be strengthened, especially in digital transactions. This research is expected to provide recommendations for the government and consumer dispute resolution institutions.